New Aspects of Quantum Electrodynamics - Tachibana, Akitomo (Springer Singapore : Imprint: Springer, 2017)
This book presents new aspects of quantum electrodynamics (QED), a quantum theory of photons with electrons, from basic physics to physical chemistry with mathematical rigor. Topics covered include spin dynamics, chemical reactivity, the dual Cauchy problem, and more. Readers interested in modern applications of quantum field theory in nano-, bio-, and open systems will enjoy learning how the up-to-date quantum theory of radiation with matter works in the world of QED. In particular, chemical ideas restricted now to nonrelativistic quantum theory are shown to be unified and extended to relativistic quantum field theory that is basic to particle physics and cosmology: realization of the new-generation quantum theory. Readers are assumed to have a background equivalent to an undergraduate student's elementary knowledge in electromagnetism, quantum mechanics, chemistry, and mathematics. .